Oral Roberts: A Religious Innovator - McBain, Robert D. (Pneuma, 2022)
The religious economy paradigm sees churches as firms, pastors as marketers, and church members as consumers whose tastes shape the goods and services the ministers offer. Religious innovators operate within this framework as suppliers who thrive because they react quickly to changing cultural and social conditions. This article argues that Oral Roberts was a religious innovator who operated and thrived within this environment because he quickly reacted to changing cultural and social conditions and resourcefully supplied and packaged his spiritual products in ways that resonated with his followers’ needs and tastes.